Rádio brincadeira: os jogos sonoros e performances do corpo nos programas infantis - Fernandes, Rodrigo Fonseca (2014)
This research investigates the tensions between the linear logic of radio production and the creative possibilities and liberating the language of radio. From the analysis of programs geared to children, we intend to demonstrate that the radio is a binding environment through sound performances from the bodies. In this way, we try to answer the following problem: to which extent the sound games present in children's programs allow the freedom of creation and disassembly of logical narrative elements among children? The goal is to understand the sound performances of the programmes in Brazilian radio stations as possible gestures of disassembly of the linear characteristics of traditional radio. The research has as corpus the following programs: Rádio Maluca and Estação Brincadeira MECRJ, both from Rádio MEC-Rio de Janeiro; Para ouvir e aprender program, broadcasted on Radio Rural de Santarém/Pará; pilot project Loja do Tio Nico, developed by students of Universidade Municipal de São Caetano do Sul; didactic audio Projeto Faz de Conta, produced by Rádio Cultura and used in schools in the State of São Paulo in Brazil. The performances were observed live from the Auditorium of Rádio Nacional, where it is broadcast Rádio Maluca program, between 2011 and 2012. The theoretical framework is based on concept of game in Huizinga and Caillois, which operates in constructions of cultural environments present in Bystrina, Wulf, Gebauer and Baitello Junior. The playful radio operation is possible through performances with sounds that have been observed in Schafer, Schaefffer, Sperber, Arnheim, Deharme e Menezes, looking for the aesthetic elements and binding present in radio soundscapes. It was observed that the games aired by radio children's programs explore the creativity of the child from elements of visuality, rather than purely sound creation